The Wandering Mind : What the Brain Does When You're Not Looking. - Corballis, Michael C. (Auckland University Press, 2014)
While psychologists write bestsellers about humans' smarter side?language, cognition, consciousness?and self-help gurus harangue us to be attentive and mindful, we all know that much of the time our minds are just goofing off. So what does the brain do when you're not looking? Rooted in neuroscience, psychology and evolutionary biology but written with Corballis's signature wit and wisdom, The Wandering Mind takes us into the world of the?default-mode network' to tackle the big questions. What do rats dream about? What's with our fiction addiction? Is the hippocampus where free will take.